Do the attributes of audit committee explain non-performing loans? evidence from an emerging economy / Arifa Akter ... [et al.] - Akter, Arifa; Hossain, Mohammad Kamal; Alam, Mohammad Jahangir; Islam, Md. Shajul (Universiti Teknologi MARA, 2021)
This study examined whether various attributes of the audit committee of listed banks in Bangladesh explain the level of non-performing loans (NPLs). This study used a panel data set comprising all 30 listed banks with 250 bank-year observations for the period 2013-2017. It employed the random-effects GLS regression model with cluster robust standard error and AR (1) disturbance to examine the effect of several audit committee attributes on NPLs. We found that holding audit committee meetings frequently and a higher number of independent members in the audit committee facilitate to reduce NPLs. We, however, find no explicit evidence that the other attributes of the audit committee examined (audit committee size, financial experience and financial literacy of the audit committee members, professional qualifications of the audit committee Chairman) contribute in reducing NPLs. The findings will be useful for policymakers of the banking sector in Bangladesh and the relevant regulatory bodies in enabling them to understand the role of the various attributes of the audit committee in the incidence of NPLs.